Shadow command - Brown, Dale, 1956- (William Morrow, 2008)
General Patrick McLanahan, commander of the new Aerospace Battle Force, ignores directives from the White House and Pentagon to stand down and orders the ABF to attack secret Russian bases in Iran in an attempt to thwart Russian aggression.